David Jacoby. Travellers, Merchants and Settlers in the Eastern Mediterranean, 11th-14th Centuries. - Ritondale, Manuela (Journal of Greek Archaeology, 2018)
The choice of a suitable title for this collection of studies, originally published by David Jacoby between 2003 and 2008, must have been challenging. As a metaphor of the partial nature of any historical or archaeological context, the mentioned categories are far from representative for the whole range of topics the volume covers, and the relationship between them is not completely straightforward at first glance.